Women's Liberation in Meiji Japan: Ruptures in Cultural Conceptions of Female Education, Social Roles, and Political Rights - Marina Teresinha De Melo Do Nascimento (Ksiegarnia Akademicka Publishing, 2020)
In 1872, the Meiji government issued the Education Act aiming to provide basic public education for boys and girls. The clash between Confucian ideals of women and the recently introduced Western literature on female liberation divided opinions among scholars. Having been influenced by the writings of British thinkers such as John Stuart Mill or Herbert Spencer, Japanese male and female thinkers proceeded to enlist various arguments in favor of female schooling and equal rights. Despite their advocating the right of women to attend schools, as well as their general agreement regarding the favorable results that girls’ education could bring to the nation, it is possible to identify key differences among scholars concerning the content of girls’ education and the nature of women’s rights. This paper focuses on Kishida Toshiko, an important female figure in Meiji politics who fought not only for female education but emerged at the forefront of activism in her advocacy of women’s political rights and universal suffrage, showing the clear influence of British suffragette Millicent Garret Fawcett.